Is Total Femur Replacement a Reliable Treatment Option for Patients With Metastatic Carcinoma of the Femur?. Issue 5 (May 2018) - Sevelda, Florian; Waldstein, Wenzel; Panotopoulos, Joannis; Kaider, Alexandra; Funovics, Philipp Theodor; Windhager, Reinhard
Abstract: Background: The majority of metastatic bone lesions to the femoral bone can be treated without surgery or with minimally invasive intramedullary nailing. In rare patients with extensive metastatic disease to the femur, total femur replacement may be the only surgical alternative to amputation; however, little is known about this approach. Questions/purposes: In a highly selected small group of patients with metastatic carcinoma of the femur, we asked: (1) What was the patient survivorship after this treatment? (2) What was the implant survivorship free from all-cause revision and amputation, and what complications were associated with this treatment? (3) What functional outcomes were achieved by patients after total femur replacement for this indication? Methods: Eleven patients (three men, eight women) with a mean age of 64 years (range, 41-78 years) received total femur replacements between 1986 and 2016; none were lost to followup. The most common primary disease was breast cancer. In general, during this period, our indications for this procedure were extensive metastatic disease precluding internal fixation or isolated proximal or distal femur replacement, and an anticipated lifespan exceeding 6 months. Our contraindication for this procedure during this time was expected lifespan less than 6 months. Patient survival was assessed by Kaplan-Meier analysis; implant survival free from revision surgery and amputation were assessed by competing risk analysis. Function was determined preoperatively and 6 to 12 weeks postoperatively with the Musculoskeletal Tumor Society (MSTS) score normalized to a 100-point scale, with higher scores representing better function from a longitudinally maintained institutional database. Results: Eleven patients died at a median of 5 months (range, 1-31 months) after surgery. One-year revision-free and limb survival were 82% (95% CI, 51%-98%) and 91% (95% CI, 61%-99%), respectively. Reasons for reoperation were hip dislocation, infection and local recurrence in one patient each. The latter two complications resulted in amputation in two patients. The median MSTS score was 32 (range, 13-57). Conclusions: Despite attempts to select patients who might have anticipated greater life expectancy, eight of 11 patients died by 6 months after surgery, and an additional two patients had undergone an amputation at 8 and at 17 months postoperatively. Most patients undergoing total femur replacement in this series did not recover from the procedure by the time they died, despite our best attempts to perform the procedure in patients whom we thought would live at least 6 months. Based on this, we believe that most patients with extensive metastatic disease to the femur should be offered palliative care, rather than major reconstruction. Level of Evidence: Level IV, therapeutic study